The time-varying price of financial intermediation in the mortgage market - Andreas Fuster; Stephanie H. Lo; Paul S. Willen (Federal Reserve Bank of Boston, 2017)
The U.S. mortgage market links homeowners with savers all over the world. In this paper, we ask how much of the flow of money from savers to borrowers actually goes to the intermediaries that facilitate these transactions. Based on a new methodology and a new administrative dataset, we find that the price of intermediation, measured as a fraction of the loan amount at origination, is large - 142 basis points on average over the 2008-2014 period. At daily frequencies, intermediaries pass on the price changes in the secondary market to borrowers in the primary market almost completely. At monthly frequencies, the price of intermediation fluctuates significantly and is highly sensitive to volume, likely reflecting capacity constraints: a one standard deviation increase in applications for new mortgages leads to a 30-35 basis point increase in the price of intermediation. Additionally, over 2008-2014, the price of intermediation increased about 30 basis points each year, potentially reflecting higher mortgage servicing costs and an increased legal and regulatory burden. Taken together, the sensitivity to volume and the positive trend led to an implicit total cost to U.S. households of about 140 billion over this period. Finally, the increases in application volume associated with "quantitative easing" (QE) led to substantial increases in the price of intermediation, which attenuated the benefits of QE to borrowers.
Keywords: E44; E52; G21; L11; 330; mortgage finance; financial intermediation; monetary policy transmission